2022
DOI: 10.5334/ijic.6009
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care for Multimorbidity Population in Asian Countries: A Scoping Review

Abstract: Background:The complex needs of patients with multiple chronic diseases call for integrated care (IC). This scoping review examines several published Asian IC programmes and their relevant components and elements in managing multimorbidity patients. Method:A scoping review was conducted by searching electronic databases encompassing Medline, Embase, Scopus, and Web of Science. Three key concepts -1) integrated care, 2) multimorbidity, and 3) Asian countries -were used to define searching strategies. Studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…As regards the management of multimorbidity, clinical guidelines provide recommendations for specific single conditions such as diabetes, asthma, and stroke and rarely take into consideration multimorbidity [20]. Nevertheless, if physicians follow single disease guidelines, duplication of unnecessary services to multiple problems can occur, leading to a significant loss of resources and a higher risk of drug interactions [21].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…As regards the management of multimorbidity, clinical guidelines provide recommendations for specific single conditions such as diabetes, asthma, and stroke and rarely take into consideration multimorbidity [20]. Nevertheless, if physicians follow single disease guidelines, duplication of unnecessary services to multiple problems can occur, leading to a significant loss of resources and a higher risk of drug interactions [21].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…In four recent systematic reviews on the effectiveness of integrated care models that included 252 studies [ 8 , 11 , 12 , 14 ] only two were conducted in Asia [ 18 , 19 ]. Lin et al identified 23 integrated care programs in 7 Asian countries; however, only one examined outpatient attendance changes, and only four examined cost changes, indicating that more research is needed for the development of integrated care programs [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated care is still in its development stages in Singapore and Asian countries, in comparison to the countries in North America and Europe [ 12 ]. Patients with PIs in Singapore are routinely reviewed by dietitians in acute care settings but rarely in the community upon discharge.…”
Section: Introductionmentioning
confidence: 99%